Ab initio predictions for polarized deuterium-tritium thermonuclear fusion - Guillaume Hupin (Nature Portfolio, 2019)
Thermonuclear fusion of nuclei of deuterium and tritium may provide the energy for the future and spin polarization is a potential mechanism for enhancing the nuclear reaction. Here the authors predict the enhanced DT fusion rate using chiral effective field theory and ab initio calculations.